2021
DOI: 10.3389/fimmu.2021.695933
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cells Dampen Airway Inflammation Through Prostaglandin E2 Receptor 4

Abstract: Emerging evidence suggests a mechanistic role for myeloid-derived suppressor cells (MDSCs) in lung diseases like asthma. Previously, we showed that adoptive transfer of MDSCs dampens lung inflammation in murine models of asthma through cyclooxygenase-2 and arginase-1 pathways. Here, we further dissected this mechanism by studying the role and therapeutic relevance of the downstream mediator prostaglandin E2 receptor 4 (EP4) in a murine model of asthma. We adoptively transferred MDSCs generated using an EP4 ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 46 publications
5
26
0
Order By: Relevance
“…These controversial studies show, that more detailed analyses are required. A recent study in 2021 by Geffen et al ( 79 ) demonstrated that prostaglandin E2 receptor 4 (EP4) agonist-primed MDSCs increased arginase-1- and nitric oxide synthase-2 production. Besides, the treatment with the EP4 agonist increased immunosuppressive activity of MDSCs on T cell responses in asthmatic mice ( 79 ).…”
Section: Immune Metabolism In the Current Centurymentioning
confidence: 99%
See 1 more Smart Citation
“…These controversial studies show, that more detailed analyses are required. A recent study in 2021 by Geffen et al ( 79 ) demonstrated that prostaglandin E2 receptor 4 (EP4) agonist-primed MDSCs increased arginase-1- and nitric oxide synthase-2 production. Besides, the treatment with the EP4 agonist increased immunosuppressive activity of MDSCs on T cell responses in asthmatic mice ( 79 ).…”
Section: Immune Metabolism In the Current Centurymentioning
confidence: 99%
“…A recent study in 2021 by Geffen et al ( 79 ) demonstrated that prostaglandin E2 receptor 4 (EP4) agonist-primed MDSCs increased arginase-1- and nitric oxide synthase-2 production. Besides, the treatment with the EP4 agonist increased immunosuppressive activity of MDSCs on T cell responses in asthmatic mice ( 79 ). As prostaglandin E2 is one of the intermediates that occur during a disrupted Krebs cycle, the investigated increase of arginase-1/nitric oxide synthase-2 can probably be attributed to changes in cellular metabolism.…”
Section: Immune Metabolism In the Current Centurymentioning
confidence: 99%
“…MDSC cell therapy may be another promising strategy in this list, especially considering its potent immunosuppressive capacity and its role in maintaining immune tolerance in transplantation and autoimmunity. Several pre-clinical studies have shown promising therapeutic effects of the adoptive transfer of MDSCs in organ transplantation, autoimmune diseases as well as in a variety of other immune-related disorders, such as cyclosporin A-induced hypertension, heart failure and asthma ( 63 , 69 , 93 100 ). Here, we briefly discuss some of the cytokines and pharmacological compounds that have been identified to promote the generation and/or activation of MDSCs in vitro / ex vivo and were applied as MDSC cell therapy.…”
Section: Pharmacological Approaches To Modulate Mdscsmentioning
confidence: 99%
“…PGE 2 , in combination with GM-CSF and either IL-4 or IL-6, was found to efficiently induce MDSCs ex vivo ( 55 , 100 ). From the four EP subreceptors (EP1-4) of PGE 2 , EP2 and EP4, and not EP1 and EP3, were found to induce MDSC development, hinting at an important role of the adenylate cyclase/cAMP/PKA/CREB signaling pathway ( 55 , 100 ).…”
Section: Pharmacological Approaches To Modulate Mdscsmentioning
confidence: 99%
See 1 more Smart Citation